Common Mechanisms Underlying the Effect of Angry Rumination on Reactive and Proactive Aggression: A Moderated Mediation Model - Hou, Yueyi (Journal of interpersonal violence, 2024)
The different influencing factors and mechanisms of the two basic kinds of aggression (i.e., reactive and proactive aggression) are salient. However, they also have common influencing factors and mechanisms, which are ignored to some extent. In addition, discovering the common mechanisms is conducive to further revealing the nature and law of aggression. To address these issues, this study tested a relational model incorporating angry rumination, moral disengagement, harm aversion, reactive aggression, and proactive aggression from the perspective of aggressive motivation. A total of 1,186 undergraduate students from eight universities were recruited. The results showed that angry rumination was significantly associated with reactive and proactive aggression. Importantly, moral disengagement acted as a common mediator, and harm aversion acted as a common moderator in the effect of angry rumination on reactive and proactive aggression. Specifically, the enhancement effects of low levels of harm aversion on these relationships are due to that it could promote the effects of angry rumination on the common mediator of moral disengagement. An aggressive motivation perspective was developed to comprehensively explain the common mediating and moderating effects. The present study contributes to a greater understanding of the mechanisms of reactive and proactive aggression and how aggressive motivations shape the model of aggressive behavior. These findings support and extend current aggression theories, especially aggression motivation theories. This study could provide insights for targeted aggression prevention interventions.